A Novel CPW-Fed UWB Antenna with Band-Stop Function - Huaming Chen; Zhengrong Li; Baiyu Li; Guangfu Sun (International Journal of Antennas and Propagation)
A novel coplanar waveguide-fed (CPW) ultrawideband (UWB) antenna with band-stop function is presented in this paper. The proposed antenna comprises a CPW-fed slot rectangular patch with an open stub ground plane, and two inverted L-shaped strip conductors are fabricated on the back plane. The overall size of the antenna is 25 × 25 × 1.6 mm2, and it achieves good impedance matching and radiation gain. Simulated and measured results show that the designed antenna operates at 2.9 GHz–13.08 GHz with band rejection in the frequency band of 7.7 GHz–9.05 GHz for satellite applications, and the proposed antenna is suitable for UWB wireless communication applications.